Ca(2+) transport properties and determinants of anomalous mole fraction effects of single voltage-gated Ca(2+) channels in hair cells from bullfrog saccule - Rodriguez-Contreras, Adrian (Blackwell Science Inc, 2002)
We studied the permeation properties of two distinct single voltage-gated Ca(2+) channels in bullfrog saccular hair cells to assess the roles of the channels as physiological Ca(2+) transporters and multi-ion pores. By varying the permeant ions (Ba(2+), Ca(2+)) and concentrations (2–70 mm), we estimated the affinity constant (K(D)) of the two channels as follows (mm): L-type channel, K(D,Ba) = 7.4 ± 1.0, K(D,Ca) = 7.1 ± 2.2 (n = 7); non-L-type channel, K(D,Ba) = 5.3 ± 3.2, K(D,Ca) = 2.0 ± 1.0 (n = 8). Using ionic concentrations close to physiological conditions (2 mm Ca(2+) and 1.0 mm Mg(2+)), the conductance of the L-type channel was ∼2 pS. We determined the mechanisms by which ions traverse the pore of these single Ca(2+) channels, using mixtures of Ba(2+) and Ca(2+) at total concentrations above (70 mm) or close to (5 mm) the K(D) of the channels. We found evidence for an anomalous mole fraction effect (AMFE) only when the total divalent ion concentration was 5 mm, consistent with a multi-ion pore. We show that AMFE arises from the boundaries between the pore and bulk solution in the atria of the channel, which is derived from the presence of depletion zones that become apparent at low divalent cation concentrations. The present findings provide an explanation as to why previous whole-cell Ca(2+) currents that were recorded in quasi-physiological Ca(2+) concentrations (∼2–5 mm) showed clear AMFE, whereas single Ca(2+) channel currents that were recorded routinely at high Ca(2+) concentrations (20–110 mm) did not.